Chinese numerical proverbs using semiotic features to describe cultural elements of ancient Chinese society - Abdul Aziz, Adi Yasran; He, Zongjin (The Global Council for Anthropological Linguistics, 2024)
As a Chinese treasure, the Chinese numerical proverb constitutes a unique linguistic term and cultural expression used by ancient Chinese people to express their cultural thoughts. The numeral conceptions in Chinese proverbs relate to Chinese philosophy and events in ancient Chinese or the whole, as a cultural symbol aligning with thought in Taoist philosophy. In past studies, many researchers focused on language comparison, and did not connect proverbs with symbols and the culture of Chinese society. Hence, this study will explore the relationship of Chinese numerical proverbs with the semiotic features of proverbs. We will analyze the cultural meanings of numerical Chinese proverbs and how the semiotic features can link to the cultural activities of ancient Chinese society. For this, we adopt symbolism theory (Zhao Yiheng 2011) and cultural symbol theory (Wu Huiyin 2013).